Myxoid Liposarcoma: Prognostic Factors and Metastatic Pattern in a Series of 148 Patients Treated at a Single Institution. (16th May 2018) - Muratori, Francesco; Bettini, Leonardo; Frenos, Filippo; Mondanelli, Nicola; Greto, Daniela; Livi, Lorenzo; Franchi, Alessandro; Roselli, Giuliana; Scorianz, Maurizio; Capanna, Rodolfo; Campanacci, Domenico
Abstract : Objectives. The authors reported a retrospective study on myxoid liposarcomas (MLs), evaluating factors that may influence overall survival (OS), local recurrence-free survival (LRFS), metastasis-free survival (MFS), and analyzing the metastatic pattern. Methods. 148 MLs were analyzed. The sites of metastases were investigated. Results. Margins (p = 0.002), grading (p = 0, 0479), and metastasis (p < 0, 0001) were significant risk factors affecting overall survival (OS). Type of presentation (p = 0.0243), grading (p = 0, 0055), margin (p = 0.0001), and local recurrence (0.0437) were risk factors on metastasis-free survival (MFS). Authors did not observe statistically significant risk factors for local recurrence-free survival (LRFS) and reported 55% extrapulmonary metastases and 45% pulmonary metastases. Conclusion. Margins, grading, presentation, local recurrence, and metastasis were prognostic factors. Extrapulmonary metastases were more frequent in myxoid liposarcoma.